Nota sobre las condiciones de transversalidad en problemas de control óptimo - Accinelli, Elvio (Pro Mathematica, 2003)
The controversial topic of which the conditions of transversality are for problems of infinite temporal horizon is presented here within the general context of the theory of Optimal Control. Results are presented for linear and autonomous case, as well as Arrow's theorem.